CHOOSING THE RIGHT METHODOLOGY FOR TEACHING ENGLISH AS A SECOND LANGUAGE - Miraximova, Mohinur; Davronova, Fariza; Zaynab, Azimjonovna (Educational Research in Universal Sciences, 2023)
Teaching English as a second language (TESL) is the practice of teaching individuals whose first language is not English how to effectively communicate in English. It is crucial to choose the right methodology when instructing English language learners in order to facilitate their language acquisition and improve their overall proficiency. This article explores various teaching methodologies to determine the most suitable approach for teaching English as a second language.